1985
DOI: 10.1002/pol.1985.170230102
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial polymerization of an isocyanate and a diol

Abstract: SynopsisThe interfacial reaction between a liquid polyfunctional aromatic isocyanate and a diol was studied using infrared spectroscopy to follow the reduction in concentration of the isocyanate group. It was shown that the product polyurethane formed a gel layer around dispersed isocyanate droplets which were swollen by the diol but not by fhe isocyanate. A model for the process is suggested based on the reaction occuring at the interface of a diminishing droplet surface. It is suggested that the reaction is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 8 publications
1
30
0
Order By: Relevance
“…In these models the reaction occurs at the interface of the two phases and the rates of diffusion of monomers A and B through the fluid phase and the polymerization zone control the rate of formation of the membrane. [8][9][10] The interfacial photopolymerization reaction described here however, refers to a polymerization process constrained to a solid surface-prepolymer interface (as it is used in cell encapsulation). [6] Therefore, the process of cell encapsulation by interfacial polymerization considered here is a surface initiated polymerization, and occurs as a result of free radical copolymerization of monomers A and B, which are both present in the aqueous phase.…”
Section: Full Papermentioning
confidence: 99%
“…In these models the reaction occurs at the interface of the two phases and the rates of diffusion of monomers A and B through the fluid phase and the polymerization zone control the rate of formation of the membrane. [8][9][10] The interfacial photopolymerization reaction described here however, refers to a polymerization process constrained to a solid surface-prepolymer interface (as it is used in cell encapsulation). [6] Therefore, the process of cell encapsulation by interfacial polymerization considered here is a surface initiated polymerization, and occurs as a result of free radical copolymerization of monomers A and B, which are both present in the aqueous phase.…”
Section: Full Papermentioning
confidence: 99%
“…This mixing is critical, as insufficient reactant contact will result in unreacted species and thus poor final material properties (Bourne and Garcia-Rosas, 1985;Kolodziej et al, 1982;Lee et al, 1980;Nguyen, 1985;Tucker Correspondence concerning this paper should be addressed to C. W. and Suh, 1980). Previous studies have concluded that the bulk fluid flow in the RIM mixhead is responsible for achieving mixing only to a reactant striation scale of 100 pm (Kolodziej et al, 1982;Pearson and Williams, 1985). There must be some process accountable for additional mixing to a scale of less than 1 pm to justify the high-quality product polymers formed in RIM.…”
Section: Introductionmentioning
confidence: 97%
“…Second order reaction at the interface No 6 Karode et al [12] (i) Mass transfer of both monomers from bulk to interface; (ii) diffusion of diamine through polymer film (i) Detailed kinetics, reaction in a zone; (ii) phase separation by spinodal decomposition MW and PD 7 Karode et al [13] (i) Mass transfer of both monomers from bulk to interface; (ii) diffusion of diamine through polymer film (i) Detailed kinetics, reaction in a zone; (ii) phase separation by nucleation and spinodal decomposition MW and PD the already-formed film and organic phase) and the entire polymer formed is assumed to form the film [10,11,14]. In the second, the reaction is assumed to occur in a reaction zone which lies on the organic side of the interface mentioned above, and the polymer formed is excluded from the reaction zone as it forms; the reaction zone gets pushed into the organic phase as the film grows [12,13,15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence [3,5,6,11,[18][19][20][21] points to a strong influence of the conditions employed in the preparation on the nature and properties of the film that forms. However, most of the models [7][8][9][10][11][14][15][16][17] focus on the kinetics and the variation of film thickness with time, and do not attempt to predict quantitatively the polymer properties as a function of process parameters. Properties such as molecular weight, polydispersity and crystallinity affect important characteristics of the polymer [20][21][22] such as mechanical properties, viscosity, ease of processing, permeability.…”
Section: Introductionmentioning
confidence: 99%